Permutation entropy and information recovery in nonlinear dynamic economic time series - Miguel Henry; George G. Judge (Econometrics, 2019)
The focus of this paper is an information theoretic-symbolic logic approach to extract information from complex economic systems and unlock its dynamic content. Permutation Entropy (PE) is used to capture the permutation patterns-ordinal relations among the individual values of a given time series; to obtain a probability distribution of the accessible patterns; and to quantify the degree of complexity of an economic behavior system. Ordinal patterns are used to describe the intrinsic patterns, which are hidden in the dynamics of the economic system. Empirical applications involving the Dow Jones Industrial Average are presented to indicate the information recovery value and the applicability of the PE method. The results demonstrate the ability of the PE method to detect the extent of complexity (irregularity) and to discriminate and classify admissible and forbidden states.
Keywords: C13; C14; C25; C51; 330; Cressie-Read divergence; information theoretic methods; complexity; nonparametric econometrics; permutation entropy; nonlinear time series; symbolic logic